Subcutaneous endometriosis associated with adenomyosis: A complex multidisciplinary surgical case - Wulandari, Riza; Saputra, Nicko Pisceski Kusika; Lubis, Munawar Adhar (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Abdominal wall endometriosis is an uncommon extrapelvic form of endometriosis, most often developing at a previous gynecologic surgical scar. Patients typically report cyclical pain with or without a palpable mass, and diagnosis is frequently delayed because the presentation can mimic hernia, granuloma, lipoma, or desmoid tumor. Purpose: To describe the clinical presentation, imaging findings, perioperative optimization, surgical management, and histopathological confirmation of abdominal wall endometriosis coexisting with adenomyosis in a patient with significant medical comorbidities. Method: A case report was performed in a 45-year-old multiparous woman with a five-year history of progressive lower abdominal pain that worsened during menstruation and localized to a prior surgical scar. Pelvic ultrasonography identified adenomyosis and a 6.9 × 3.9 cm hypoechoic lesion in the anterior abdominal wall, raising suspicion of subcutaneous endometriosis. Results: Surgical exploration showed a lesion extending through the subcutaneous tissue and fascia, with focal involvement of the rectus muscle. Complete excision was achieved after preoperative optimization, and the postoperative course was uneventful. Histopathological examination of two specimens (9 × 6 × 4 cm and 5 × 2 × 1 cm) demonstrated fibrocollagenous tissue, adipose tissue, and skeletal muscle infiltrated by endometrial glands, confirming abdominal wall endometriosis. Conclusion: Abdominal wall endometriosis should be considered in women presenting with cyclical pain at a surgical scar. Imaging supports assessment of lesion extent and surgical planning, while histopathology remains essential to confirm the diagnosis and to exclude rare malignant transformation.